Role of Estimation of Total Length of Femur from its Fragments on Medico-legal Cases (Indian Internet Journal of Forensic Medicine and Toxicology, 2012)
In most forensic anthropological investigations, stature is estimated using the combined dimensions of bones responsible for living stature or using regression equations based on complete long bone length measurements. However, in mass disasters, burns and in skeletal cases where many of these bones are carried off by the animalsthese methods cannot be applied because intact long bones are not available. As a result anthropologists have developed methods for reconstructing stature based on measurements of fragments of long bones. From these measurements bone length is estimated and then the estimated bone length is used to estimate stature. This study was done on 162 grossly normal and completely ossified femora (86 males and 76 females femora) taken from osteology sections of the departments of Anatomy and Forensic Medicine, SGRDIMSAR, Amritsar. With the help of improvised osteometric board the maximum total length of all the femora and linear, transverse, sagital and circumferential measurements of the segments were taken simultaneously. The ranges, arithmetic means, standard deviations, correlation coefficient and regression equations were then calculated with the help of stature formulae, the length so calculated may be used in determining the probable stature of a person. In conclusion, our study demonstrated that length of femur can be estimated from measures of different segments of bone.
Keywords: Femur length; Fragmentary measurements; Stature; Regression equation